FPM PADA KELUARGA EKSPONENSIAL BENTUK KONONIK - Puspita, Entit (Jurnal Pengajaran MIPA, 2002)
We can determine the distribution of the random variable by considering its moment generating function (MGF). Unfortunately there are some distribution which have no MGF. This kind of the problem cann’t occur on an exponential family, because the comunic form of the family always can be determined its MGF.